Co-Production and Co-Creation Engaging Citizens in Public Services - Brandsen, Taco; Steen, Trui; Verschuere, Bram (Routledge Critical Studies in Public Management, 2018)
Co-production and co-creation occur when citizens participate actively in delivering and designing the services they receive. It has come increasingly onto the agenda of policymakers, as interest in citizen participation has more generally soared. Expectations are high and it is regarded as a possible solution to the public sector's decreased legitimacy and dwindling resources, by accessing more of society's capacities. In addition, it is seen as part of a more general drive to reinvigorate voluntary participation and strengthen social cohesion in an increasingly fragmented and individualized society. Co-Production and Co-Creation: Engaging Citizens in Public Services offers a systematic and comprehensive theoretical and empirical examination of the concepts of co-production and co-creation and their application in practice. It shows the latest state of knowledge on the topic and will be of interest to students at an advanced level, academics and reflective practitioners. It addresses the topics with regard to co-production and co-creation and will be of interest to researchers, academics, policymakers, and students in the fields of public administration, business administration, economics, political science, public management, political science, service management, sociology and voluntary sector studies.